2021
DOI: 10.1002/da.23145
|View full text |Cite
|
Sign up to set email alerts
|

Moral injury and suicidal behavior among US combat veterans: Results from the 2019–2020 National Health and Resilience in Veterans Study

Abstract: Background: Recent research suggests that exposure to potentially morally injurious experiences (PMIEs) may be associated with increased risk for suicidal behavior among US combat veterans, but population-based data on these associations are scarce. This study examined the association between PMIEs with current suicidal ideation (SI), lifetime suicide plans (SP), and suicide attempts (SA) in a contemporary, nationally representative sample of combat veterans. Methods: Data were analyzed from the 2019-2020 Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 44 publications
(72 reference statements)
1
26
1
Order By: Relevance
“…Our findings indicated that veterans reporting higher PMIE-Self and PMIE-Betrayal levels also reported significantly higher levels of SI and depression. These results align with several studies (e.g., Nichter et al, 2021;Zerach & Levi-Belz, 2021) and the MI theoretical model (Litz et al, 2009), demonstrating the deleterious effects of PMIE exposure among veterans. Moreover, self-disclosure was found to contribute negatively to current SI among veterans, beyond the contribution of PMIEs and depression.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings indicated that veterans reporting higher PMIE-Self and PMIE-Betrayal levels also reported significantly higher levels of SI and depression. These results align with several studies (e.g., Nichter et al, 2021;Zerach & Levi-Belz, 2021) and the MI theoretical model (Litz et al, 2009), demonstrating the deleterious effects of PMIE exposure among veterans. Moreover, self-disclosure was found to contribute negatively to current SI among veterans, beyond the contribution of PMIEs and depression.…”
Section: Discussionsupporting
confidence: 91%
“…First, we computed descriptive statistics for the sample to summarize sociodemographic, military, clinical, and MIES characteristics. Second, we examined the association between exposure to three types of PMIEs (perpetration, witnessing, and betrayal subscales of the MIES) with lifetime and past-year AUD, DUD, and SUD in a series of multivariable logistic regression analyses; consistent with prior work (Nichter et al, 2021;Wisco et al, 2017), models adjusted for sociodemographic characteristics, combat exposure severity, lifetime trauma exposure, and lifetime PTSD and MDD. Prior to regression analyses, we conducted independentsamples t tests to compare MIES subscale scores in each of the dependent variable groups (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…exposure to PMIEs is associated with greater severity of PTSD and MDD symptoms, as well as heightened risk for suicidal thoughts and behaviors (Griffin et al, 2019;Maguen et al, 2020a, b;Nichter, Norman, Maguen, & Pietrzak, 2021;Wisco et al, 2017). Although researchers have speculated that moral injury may be linked to a greater likelihood of substance use disorders (SUDs; e.g.…”
mentioning
confidence: 99%
“…Post-traumatic stress disorder (PTSD) is a highly debilitating psychiatric condition that adversely affects mood, cognition, physical and emotional health, and can lead to suicidal ideation and behavior [1][2][3][4]. In any given year, 3.5-4.7% of US adults or about 7.3-9.8 million individuals experience PTSD.…”
Section: Introductionmentioning
confidence: 99%